A construção de corpos e feminilidades : travestis e transexuais para além da prostituição - Pessoa, Emerson Roberto de Araujo (2013)
This research aims to understand the embodiment and femininity's construction developed by transvestites and transsexuals who do not take part in the sex market. Through Oral History, it was researched how medical technologies (silicones, hormones), as well as apparel and other accessories are used on femininity production by trans-individuals. The objective of this workwas to measure the differences between the researched group and the Brazilian anthropological bibliography. The results enabled to understand the social relations of theresearched group's life trajectory. These relations implicate some aspects like familiar support, secondary school completion and the professional performance which does not involve the sex market. The biotechnologies contribute to the production of femininesubjectivity and their positive self-image. The embodiment's constructions and femininitiesare carried out through an internalization of feminine view which permeates trans-individual's life experience. Therefore, there is not only one specific way of building these traits; for, they are developed through habits. The cultural and economical capitals, as well as scientific medical speech contribute to the production of these subjectivities. Thus, a corporeal construction was noticed directed not only to hegemonic models. This way, such trajectories of life demonstrate new configurations of trans-corporeality..